2005
DOI: 10.1007/s00268-005-7729-9
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Autotransplantation during Total Thyroidectomy—Does the Number of Glands Transplanted Affect Outcome?

Abstract: Parathyroid autotransplantation is a technique for ensuring the continued function of parathyroid tissue at the time of total thyroidectomy (TT). The aim of this study was to ascertain whether the number of parathyroids transplanted affects the incidence of temporary and permanent hypoparathyroidism. A retrospective cohort study included all patients undergoing a TT in a single unit between July 1998 and June 2003. The number of parathyroids transplanted, the final pathology, and the incidence of temporary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 35 publications
3
95
1
6
Order By: Relevance
“…A large retrospective study comparing the occurrence of hypoparathyroidism after autotransplantation of 0, 1, 2, or 3 parathyroid glands following total thyroidectomy found 9.8%, 11.9%, 15.1%, and 31.4% (P<.05) incidence rates of temporary hypoparathyroidism respectively; the corresponding rates for permanent hypoparathyroidism were 0.98%, 0.77%, 0.97%, and 0% (P>.05) (19). The principal value of parathyroid autotransplantation is in the prevention of permanent hypoparathyroidism.…”
Section: Parathyroid Preservation/autotransplantationmentioning
confidence: 99%
“…A large retrospective study comparing the occurrence of hypoparathyroidism after autotransplantation of 0, 1, 2, or 3 parathyroid glands following total thyroidectomy found 9.8%, 11.9%, 15.1%, and 31.4% (P<.05) incidence rates of temporary hypoparathyroidism respectively; the corresponding rates for permanent hypoparathyroidism were 0.98%, 0.77%, 0.97%, and 0% (P>.05) (19). The principal value of parathyroid autotransplantation is in the prevention of permanent hypoparathyroidism.…”
Section: Parathyroid Preservation/autotransplantationmentioning
confidence: 99%
“…Evaluation of the blood supply to the parathyroid capsule by making an incision, examination of blood flow by Doppler ultrasound, and intraoperative PTH measurements are within recommended methods in this regard. However, an ideal marker has not yet been identified (16). Therefore, parathyroid autotransplantation has been recommended whenever the function of the parathyroid gland is suspicious.…”
Section: Discussionmentioning
confidence: 99%
“…Kihara found the rate of permanent hypoparathyroidism in patients with autotransplantation as 21%, and reported that the PTH levels fall to 50% of the preoperative value in 5-year long-term follow-up. It is also noted that the routine practice of autotransplantation increases the rate of transient hypocalcemia in several studies (16,26). However, there is no agreement in the literature on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,14,15 Some parathyroid glands may be anatomically intact; however, their function may nevertheless be physiologically impaired because of parathyroid arteria occlusion or edematous gland. 16,17 Intraoperative change of the colour of parathyroid is believed to be an indicator of insufficient blood supply; however, Ander et al proved that the disorders in the microcirculation of parathyroid glands are not related to their macroscopic appearance. 18 We claim that, in our case, the experience of the surgeon could not significantly affect the outcome of surgery because both surgeons applied similar surgical procedures and were also equally skilled.…”
Section: Discussionmentioning
confidence: 99%